Bis(silylene)‐Stabilized Monovalent Nitrogen Complexes. Issue 49 (28th September 2020) - Yao, Shenglai; Szilvási, Tibor; Xiong, Yun; Lorent, Christian; Ruzicka, Ales; Driess, Matthias
Abstract: The first series of bis(silylene)‐stabilized nitrogen(I) compounds is described. Starting from the 1, 2‐bis(N‐heterocyclic silylenyl) 1, 2‐dicarba‐closo‐dedocaborane(12) scaffold 1, [1, 2‐(LSi)2 C2 B10 H10 ; L=PhC(N t Bu)2 ], reaction with adamantyl azide (AdN3 ) affords the terminal N‐μ2 ‐bridged zwitterionic carborane‐1, 2‐bis(silylium) AdN3 adduct 2 with an open‐cage dianionic nido‐C2 B10 cluster core. Remarkably, upon one‐electron reduction of 2 with C8 K and liberation of N2 and adamantane, the two silylene subunits are regenerated to furnish the isolable bis(silylene)‐stabilized N I complex as an anion of 3 with the nido‐C2 B10 cluster cage. On the other hand, one‐electron oxidation of 2 with silver(I) yields the monocationic bis(silylene) N I complex 4 with the closo‐C2 B10 cluster core. Moreover, the corresponding neutral N I radical complex 5 results from single‐electron transfer from 3 to 4 . Abstract : Starting from the unusual end‐on neutral bis(silylium) nido ‐carborane N3 Ad adduct 1, one‐electron reduction with KC8 in the presence of 18‐c‐6 leads to the K(18‐C‐6) salt 2 with the first anionic N I complex and a bis(silylenyl) nido ‐carborane ligand scaffold. One‐electron oxidation of 1 with silver(I) affords the cationic N I complex 3, which features a bis(silylenyl) closo ‐carborane ligand. Ad=adamantyl; 18‐C‐6=18‐crown‐6.